Synthesis and Antifungal Activities of 2-Amino-3-cyano-4- (2-aryl)-8-(2-arylidine)cyclohexyl pyridines Derivatives - TRIPATHI, PRAVEEN; PANDEY, SUDHA (Asian Journal of Chemistry, 2010)
The compounds 2-amino-3-cyano-4-(2-aryl)-8-2-(arylidine)- cyclohexyl pyridines were synthesized. The newly synthesized compounds shows antifungal activity against Aspergillus niger and Asperigillus flavus.